Answer:
1. 2(k + 3)
2. 3. 75 + k
Step-by-step explanation:
1. 2x + 6
Since, 2 is a common factor of 2 and 6, we can take that common outside.
So, 2x + 6 = 2(x + 3)
Note that in the initial expression, this 2 was distributed to arrive at 2x + 6.
2. (1.5 + k) + 2.25
This is simple addition. We can simply remove the brackets to have:
1.5 + k + 2.25
Since, the like terms can be added, we will have:
1.5 + 2. 25 + k
= 3. 75 + k
106.78/.05=2135.6
21356*.05=106.78
You would:
(4 * 2 - 4) + (3 - 2^2) + (2 * 2^3)
(8 - 4) + (3 - 4) + (16)
4 + -1 + 16 = 19